Vygotsky in the digital society - Ana Borgobello; Natalia Monjelat (Perspectivas Metodológicas​)
The article presents a descriptive, multivariate and content analysis of publications that deal with Vygotsky and ICT, seeking to explore what of his theory underlies current research and different uses of his ideas and approaches. The main results show references to Vygotsky in introductory sections as a general framework and in methodological sections from contextualized studies with emphasis on processes. Moreover, heuristic uses of apparently Vygotskyan concepts were identified, but from other authors or recent publications. It is evident the need to resort to reliable versions and critical readings of the Vygotskyan work if it is to continue its legacy.